Surface degradation of glass ceramics after exposure to acidulated phosphate fluoride - Vanessa Z.S. Ccahuana; Mutlu Özcan; Alfredo M. M. Mesquita; Renato S. Nishioka; Estevão T. Kimpara; Marco A. Bottino (University of São Paulo, 2010)
OBJECTIVE: This study evaluated the surface degradation effect of acidulated phosphate fluoride (APF) gel exposure on the glassy matrix ceramics as a function of time. MATERIAL AND METHODS: Disc-shaped ceramic specimens (N = 120, 10/per ceramic material) were prepared in stainless steel molds (inner diameter: 5 mm, height: 2 mm) using 6 dental ceramics: 3 indicated for ceramic-fused-to-metal (Vita Omega 900, Carmen and Vita Titankeramik), 2 for all-ceramic (Vitadur Alpha and Finesse® Low Fusing) and 1 for both types of restorations (IPS d.SIGN). The specimens were wet ground finished, ultrasonically cleaned and auto-glazed. All specimens were subjected to calculation of percentage of mass loss, surface roughness analysis and topographical description by scanning electron microscopy (SEM) before (0 min) and after exposure to 1.23 % APF gel for 4 min and 60 min representing short- and long-term etching effect, respectively. The data were analyzed using two-way ANOVA with repeated measures and Tukey's test (a=0.05). RESULTS: Significant effect of the type of the ceramics (p=0.0000, p=0.0031) and exposure time (p=0.0000) was observed in both surface roughness and percentage of mass loss values, respectively. The interaction factor between both parameters was also significant for both parameters (p=0.0904, p=0.0258). Both 4 min (0.44±0.1 - 0.81±0.2 mm) and 60 min (0.66±0.1 - 1.04±0.3 mm) APF gel exposure created significantly more surface roughness for all groups when compared to the control groups (0.33±0.2 - 0.68±0.2 mm) (p<0.05). There were no significant differences in percentage of mass loss between the ceramics at 4 min (p>0.05) but at 60 min exposure, IPS d.SIGN showed the highest percentage of mass loss (0.1151±0.11). The mean surface roughness for Vita Titankeramik (0.84±0.2 mm) and Finesse® Low Fusing (0.74.±0.2 mm) was significantly higher than those of the other ceramics (0.59±0.1 mm - 0.49±0.1 mm) and Vita Titankeramik (p<0.05) regardless of the exposure time. A positive correlation was found between surface roughness and percentage of mass loss for all ceramic materials [(r=0.518 (Vitadur Alpha), r=0.405 (Vita Omega 900), r=0.580 (Carmen), r=0.687 (IPS d.SIGN), r=0.442 (Finesse® Low Fusing), r=0.572 (Vita Titankeramik), Pearson's correlation coefficient)]. The qualitative SEM analysis showed evidence of corrosive attack on all of ceramics at varying degrees. CONCLUSIONS: The ceramics indicated for either metal-ceramic or all-ceramic restorations were all vulnerable to surface texture changes and mass loss after short-term and long-term APF gel exposure.